2018
DOI: 10.1177/0269215518757050
|View full text |Cite
|
Sign up to set email alerts
|

Pain Exposure Physical Therapy versus conventional treatment in complex regional pain syndrome type 1—a cost-effectiveness analysis alongside a randomized controlled trial

Abstract: Objective:To analyze cost-effectiveness of Pain Exposure Physical Therapy compared to conventional treatment alongside a randomized controlled trial (NCT00817128) in patients with complex regional pain syndrome type 1, where no clinical difference was shown between the two groups in an intention-to-treat analysis.Design:Randomized controlled trial with 9 months follow-up.Setting:Patients were recruited from hospitals and general practitioners in the region around a university hospital.Subjects:A total of 56 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 23 publications
0
27
0
Order By: Relevance
“…The pathologies covered by the largest number of studies were stroke with 21 studies (representing 48.8%), Parkinson’s disease with 6 studies (13.9%) and multiple sclerosis with 5 studies (11.6%). Only one study was published on the other eight pathologies, with the exception of complex regional pain syndrome with two studies [ 13 , 14 ]. On the other hand, two articles were found that included heterogeneous groups of patients with neurological disorders [ 15 , 16 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathologies covered by the largest number of studies were stroke with 21 studies (representing 48.8%), Parkinson’s disease with 6 studies (13.9%) and multiple sclerosis with 5 studies (11.6%). Only one study was published on the other eight pathologies, with the exception of complex regional pain syndrome with two studies [ 13 , 14 ]. On the other hand, two articles were found that included heterogeneous groups of patients with neurological disorders [ 15 , 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, QALY was measured in all the studies conducting cost-utility analysis [ 13 , 14 , 17 , 18 , 20 , 21 , 22 , 27 , 28 , 31 , 32 , 34 , 39 , 40 , 41 , 42 , 43 , 46 , 49 , 50 , 51 , 54 ]. Other health outcomes were used including HRQL [ 14 , 27 , 28 , 31 ], daily life activities [ 22 , 52 ] or pain [ 13 ]. In other studies, we could find variables related to the pathology in the study, including balance and gait speed [ 40 ] and number of falls avoided due to the intervention in studies for Parkinson participants [ 32 , 43 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…2 In a more recent paper using an intention-to-treat analysis, we further showed that PEPT is less expensive and thereby more costeffective than conventional treatment. 3 In that study, patients who received PEPT had fewer visits to physical therapists and other healthcare providers.…”
Section: To the Editormentioning
confidence: 88%
“…It was shown to be a good and cost-effective treatment for patients with CRPS-1 in the upper or lower extremity. 19,[27][28][29][30] In addition to disuse, catastrophic thinking (ie, negative beliefs about pain leading to an overprotective response) is another factor that can lead to disproportionate pain and CRPS-1 after a fracture. Catastrophic thinking has often been correlated with chronic pain, disuse, and CRPS-1.…”
Section: Discussionmentioning
confidence: 99%